Flexibly tailored microstructure and tribological properties of carbon/carbon composites via combination of h-BN powdered addition and heat-treatment. Issue 16 (November 2019) - Li, Jinwei; Li, Yang; Li, Zhuan; Zhang, Bengu; Chen, Pengju; Niu, Zibo; Li, Zhichao; Xiao, Peng
Abstract: In this work, hexagonal boron nitride powders (h-BN) and heat-treatment (HT) were used to tailor microstructures and tribological properties for Carbon/Carbon composites. The microstructures and tribological behaviors of virgin Carbon/Carbon, h-BN modified Carbon/Carbon, Carbon/Carbon after HT, and Carbon/Carbon modified by h-BN with HT were investigated. Results indicate that h-BN powdered addition as matrix leads to PyC matrix with higher texture degree, graphitization and micro-hardness, compared to virgin Carbon/Carbon composites. Moreover, compared to virgin Carbon/Carbon, the coefficient of friction (COF) of h-BN modified Carbon/Carbon composites are increased to 0.29 while wear rates (WR) are decreased to 1.65 μm·side −1 ·circle −1 . However, the Carbon/Carbon composites modified by h-BN and HT presented quite lower COF and WR, in comparison to virgin Carbon/Carbon and Carbon/Carbon after HT. In summary, flexibly tailored COF and WR could be achieved via BN powdered addition and/or HT.